Ekplorasi Peran Investasi Asing dalam Perekonomian Internasional Indonesia - Alfiannisa’ Septisa T. A; Agung Efendi; Anizul Anwar; Sandika Darma W. P; Muhammad Bin Taga (CV. ITTC INDONESIA, 2025)
This study explores the role of foreign investment in Indonesia’s international economy. Foreign Direct Investment (FDI) plays a crucial role not only as a source of capital but also through technology transfer, managerial capacity building, and broader access to global markets. With its abundant natural resources and large domestic market, Indonesia has sought to attract FDI through regulatory reforms, fiscal incentives, and investment facilitation. The findings indicate that the contribution of FDI to economic growth is not always linear, as it depends on domestic factors such as human capital quality, political-economic stability, and infrastructure. Nevertheless, excessive reliance on FDI poses risks, including multinational dominance and unequal distribution of benefits. Therefore, a balanced strategy is required to align global investment openness with national interests and equitable development.